Soluble maize fibre affects short-term calcium absorption in adolescent boys and girls: a randomised controlled trial using dual stable isotopic tracers. Issue 3 (22nd May 2014) - Whisner, Corrie M.; Martin, Berdine R.; Nakatsu, Cindy H.; McCabe, George P.; McCabe, Linda D.; Peacock, Munro; Weaver, Connie M.
Abstract : Soluble maize fibre (SCF) has been found to significantly improve bone mineral density and strength in growing rats compared with several other novel prebiotic fibres. The objective of the present study was to investigate the effect of SCF on Ca absorption and retention in pubertal children by studying the potential absorption mechanisms of the intestinal microbiota. A total of twenty-four adolescent boys and girls (12–15 years) participated in two 3-week metabolic balance studies testing 0 g/d SCF (control (CON) treatment) and 12 g/d SCF (SCF treatment) in a random order by inclusion in a low-Ca diet (600 mg/d). Fractional Ca absorption was measured at the end of the two intervention periods using a dual-stable isotope method. Diet composites and faecal and urine samples were collected daily and analysed for Ca content. Ca retention was calculated as dietary Ca intake minus Ca excretion in faeces and urine over the last 2 weeks. Microbial community composition in the faecal samples collected at the beginning and end of each session was determined by 454 pyrosequencing of the PCR-amplified 16S ribosomal RNA gene. Fractional Ca absorption was 12 % higher (41 mg/d) after the SCF treatment compared with that after the CON treatment (0·664 (sd 0·129) and 0·595 (sd 0·142), respectively; P = 0·02), but Ca retention was unaffected. The average proportion of bacteria of the phylum Bacteroidetes was significantly greater in the participants after the SCF treatment than after the CON treatment. These results suggest that moderate daily intake of SCF, a well-tolerated prebiotic fibre, increases short-term Ca absorption in adolescents consuming less than the recommended amounts of Ca.